2015
DOI: 10.1080/10508422.2015.1043367
|View full text |Cite
|
Sign up to set email alerts
|

Do Personal Dispositions Affect the Relationship Between Psychosocial Working Conditions and Workplace Bullying?

Abstract: A c c e p t e d M a n u s c r i p t 2 ABSTRACT There is scarce research on the interaction between psychosocial working conditions and being a target of workplace bullying with individual characteristics as a moderator. We therefore examined 3363 employees from 60 Danish workplaces to test whether sense of coherence moderates the relationship between the job demand-control model and bullying. This work is exploratory in nature, as no previous study to assess this moderation was found. Hierarchical linear regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…The motivation behind bullying behavior is poorly understood through the ecological systems model, however it is suggested that bullying behavior could be motivated due to selfesteem issues, social competence, poor leadership skills along with micro political behavior to advance one's career (Einarsen et al, 2003;Glasø et al, 2009). At the micro level, outcomes of workplace bullying for the target includes mental health problems including depression (Emdad et al, 2013), anxiety (Farmer, 2011), sleep issues (Nielsen & Einarsen, 2012) and post-traumatic stress disorder (Nielsen, Tangen, et al, 2015) along with negative physical health outcomes including cardiovascular disease (Rooyen & McCormack, 2013).…”
Section: Framework Of Workplace Bullyingmentioning
confidence: 99%
“…The motivation behind bullying behavior is poorly understood through the ecological systems model, however it is suggested that bullying behavior could be motivated due to selfesteem issues, social competence, poor leadership skills along with micro political behavior to advance one's career (Einarsen et al, 2003;Glasø et al, 2009). At the micro level, outcomes of workplace bullying for the target includes mental health problems including depression (Emdad et al, 2013), anxiety (Farmer, 2011), sleep issues (Nielsen & Einarsen, 2012) and post-traumatic stress disorder (Nielsen, Tangen, et al, 2015) along with negative physical health outcomes including cardiovascular disease (Rooyen & McCormack, 2013).…”
Section: Framework Of Workplace Bullyingmentioning
confidence: 99%
“…This indicates that responses to workplace bullying may be moderated by employees' personal characteristics. It is clear that personal characteristics may influence the way employees perceive and deal with workplace bullying, as well as the outcomes that result from this experience (Francioli et al, 2016), but empirical studies are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying has been increasingly recognized as a serious problem in the working environment (Francioli et al 2016). Bullying and harassment are reported to happen regularly in many work organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have focused on work environment variables as antecedents of workplace bullying (Samnani & Singh 2016). However, several studies have provided empirical support for the assumption that certain psychosocial factors at work may foster bullying in the workplace (Francioli et al 2016;Hauge, Skogstad & Einarsen 2009). Aquino and Thau (2009) asserted that research on personality factors at the individual level remained inconclusive.…”
Section: Introductionmentioning
confidence: 99%